2011
DOI: 10.1017/s0305004111000132
|View full text |Cite
|
Sign up to set email alerts
|

Springer representations on the Khovanov Springer varieties

Abstract: Springer varieties are studied because their cohomology carries a natural action of the symmetric group $S_n$ and their top-dimensional cohomology is irreducible. In his work on tangle invariants, Khovanov constructed a family of Springer varieties $X_n$ as subvarieties of the product of spheres $(S^2)^n$. We show that if $X_n$ is embedded antipodally in $(S^2)^n$ then the natural $S_n$-action on $(S^2)^n$ induces an $S_n$-representation on the image of $H_*(X_n)$. This representation is the Springer represent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…The proof of simple-connectivity is essentially the same as Seidel-Smith's proof that H 1 (Y n ) = 0 [53,Lemma 44]: as explained there (see also [53,Section 2.3]), Y n is diffeomorphic to the (n, n) Springer variety B n,n . Russell and Tymoczko [48,Theorem 5.5] and Wehrli [62,Theorem 1.2] showed that B n,n is homeomorphic to the space S := a S a ⊂ (CP 1 ) 2n where the union is over all isotopy classes a of upper half-plane crossingless matchings a, viewed as involutions a : {1, . .…”
Section: A Brief Review Of Symplectic Khovanov Homologymentioning
confidence: 99%
“…The proof of simple-connectivity is essentially the same as Seidel-Smith's proof that H 1 (Y n ) = 0 [53,Lemma 44]: as explained there (see also [53,Section 2.3]), Y n is diffeomorphic to the (n, n) Springer variety B n,n . Russell and Tymoczko [48,Theorem 5.5] and Wehrli [62,Theorem 1.2] showed that B n,n is homeomorphic to the space S := a S a ⊂ (CP 1 ) 2n where the union is over all isotopy classes a of upper half-plane crossingless matchings a, viewed as involutions a : {1, . .…”
Section: A Brief Review Of Symplectic Khovanov Homologymentioning
confidence: 99%
“…Khovanov and Kuperberg constructed a bijection between Young tableaux of shape (n, n, n) and irreducible webs for sl 3 for which each boundary vertex is a source [4]. However, unlike our direct map, Khovanov-Kuperberg's proof uses a complicated set of growth rules which, when recursively applied, eventually generate all irreducible webs for sl 3 . Our work is motivated by the geometry of the (n, n, n) Springer variety and generalizes earlier work on the (n, n) Springer variety of Fung [2] and of the author with Russell [10]. In that context, a web's boundary vertices correspond to the nested vector spaces of an element in the full flag variety, and edges correspond to lines in the vector space C 2n .…”
mentioning
confidence: 97%
“…( Remark 5. In contrast to the related work [RT11] in type A we work with the entire homology and identify it as an induced representation. This approach has the following advantages:…”
Section: Theorem Cmentioning
confidence: 99%
“…Remark 11. The white dots in this article play exactly the same role as the black dots on the cup diagrams in the related work in type A, [RT11], [Rus11]. In order to distinguish them from the black markers (which do not appear in type A) we chose to color them white.…”
Section: A Diagrammatic Homology Basis and The Proof Of Theorem Dmentioning
confidence: 99%